Adsorption of organic peroxides on the surface of amourphous alloys for the drugs immobilization - Hertsyk, O.M.; Hula, T.H.; Kovbuz, M.O.; Pandiak, N.L.; Ezers’ka , O.A. (Physics and Chemistry of Solid State, 2022)
It was investigated wetting of surfaces of the amorphous metallic alloys (AMA) based on iron and cobalt with aqueous-ammonium solutions of oligoperoxides based on vinyl acetate, 2-tert-butylperoxy-2-methyl-5-hexen-3-yne and maleic anhydride (OP-1) and based on vinyl acetate, 3-tert-butylperoxy-3-phenylbutylmethacrylate and maleic anhydride (OP-2). The surface tension of thin films of oligoperoxideʼs aqueous-ammonia solutions was determined and were calculated values of the macromolecules adsorption. A higher surface activity of OP-2 was observed in comparison with OP-1. The values ​​of the adhesion work between contact and external metallic surfaces and solutions of oligomers were calculated.